PERAN STRATEGI PROMOSI DALAM MENINGKATKAN VOLUME PENJUALAN PADA PT ALFAMART KUTACANE - Desy Lopiga; Nasruddin Nasruddin; Bahrul Ilmi (Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
In an effort to retain its customers, PT. Alfamart is required to be responsive and meticulous in understanding customer desires and satisfaction. Alfamart runs weekly promotions every month. The researcher wanted to determine whether these weekday promotional prices have an impact. Meanwhile, with the increasing competition, minimarkets in Medan often publish brochures containing promotional prices at specific times. The purpose of this study was to determine and analyze "The Role of Promotional Strategies in Increasing Sales Volume at PT. Alfamart Kutacane." This study used a quantitative approach, a research method based on the philosophy of positivism, to examine a specific population or sample. The data source was consumers shopping at Alfamart Kutacane by distributing questionnaires, and respondents' answers were measured using a Likert scale. Secondary data, sourced from the company, included sales data, a general overview of the company, and its organizational structure. The collected data was analyzed using SPSS software, consisting of descriptive statistical tests, classical assumption tests, simple linear regression, and partial hypothesis tests and coefficients of determination. The results showed that promotion partially had a positive and significant effect on sales volume at PT Alfamart Kutacane. The adjusted R-square value was 0.514, indicating that the promotion variable could explain 51.4% of the variation in sales volume at PT Alfamart Kutacane, while the remaining 48.6% was explained by independent variables not examined, such as service quality and promotion.